(untitled) (Faridpur Medical College Journal, 2017)
A quasi experimental study was carried out among 60 stage III NSCLC patients attending at Radiation Oncology Department of National Institute of Cancer Research & Hospital, Mohakhali, Dhaka from August 2012 to July 2013. Patients were divided into group A and group B purposively to receive Induction Chemotherapy followed by conventional or 3D CRT respectively. The study was designed to observe the radiological response and acute toxicity of stage III NSCLC with induction CT and 3DCRT. Treatment related morbidity was more observed in the intervention group with 43.3% Grade ?2 Pneumonitis, 43.4% Grade ?2 Oesophagitis, 40% Grade 2 skin toxicity and 6.7% Grade?3 anemia. Regarding metastasis, 33.3% patients in the intervention arm and 30% patients in the control arm had presented with metastasis at different sites within this six months period. No statistically significance was found between these two groups (p = .781). Death during follow up was observed in 6.7% patients in the intervention group and 3.3 % patients in the control arm which was of no statistically significance difference. (p = 1.00). Complete response was found in 23.3 % patients in intervention group while in control group it was only 6.7%. Partial response was 46.7% and 43.3% respectively. No response was seen in 36.6% patients; 13.3% in the intervention group and 23.3% in the control group. More patients in control group (26.7%) were reported with progressive disease. No statistical significance was found regarding the radiological response between these two arms (p=.114). Both complete and overall responses were better in intervention group than control group. Faridpur Med. Coll. J. Jan 2017;12(1): 18-24